Pengaruh Servant Leadership dan Pemberdayaan Terhadap Kinerja Pegawai Dimoderasi Lingkungan Kerja - Zubaidi Mukhlis; Marlien; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the influence of servant leadership and empowerment on employee performance moderated by the work environment. The research was conducted at the Dinas Kelautan dan Perikanan Kabupaten Pati using all employees of the Dinas Kelautan dan Perikanan Kabupaten Pati as a population. Census sampling technique is used in the research. Data analysis was performed using SPSS software version 27.0. Results showed that servant leadership significantly affect to performance. Empowerment does not affect significantly to employee performance. Work environment moderates the relationship between leadership and empowerment to employee performances. The study has theoretical and practical implication